Hyperbranched bio-based siloxane composite nanodefoamer and preparation method thereof
Patent Information
- Application Number
- CN202611212622.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-08-11
AI Technical Summary
[0003]但是,传统硅醚消泡剂仍存在技术瓶颈
本发明的超支化生物基硅醚复合纳米消泡剂,摒弃传统线性聚醚结构,采用蓖麻油多元醇与柠檬酸真空减压缩聚,构建高支化度多元醇内核,高支化多羟基结构具备大量活性反应位点,后续与生物基环氧丙烷开环聚合、烯丙基封端后,形成多分支、多双键的超支化生物基聚醚。相较于传统线性聚醚,本发明超支化生物基聚醚具有较多支链和末端官能团,可提供多个界面吸附及反应位点,有利于改善其与硅氧烷组分的相容性、界面吸附能力和体系分散稳定性,从而降低长期储存过程中发生分层和漂油的风险。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of defoamer technology, specifically a hyperbranched bio-based silicone ether composite nano defoamer and its preparation method. Background Technology
[0002] Traditional silicone ether defoamers typically refer to polyether-modified polysiloxane defoamers. Their molecular structure incorporates polyether segments onto polysiloxane (silicone oil), making them unique nonionic surfactants. These defoamers combine the strong defoaming properties of silicone with the excellent foam suppression and dispersing properties of polyethers, thus finding wide application in numerous industrial fields such as cleaning, textiles, papermaking, building materials, water treatment, and petrochemicals.
[0003] However, traditional silicone ether defoamers still face technical bottlenecks. First, existing products mostly employ a preparation route of direct physical compounding of linear polyethers and silicone oils. The two phases lack stable chemical bonds, resulting in limited compatibility. Long-term storage easily leads to problems such as stratification, oil drift, and failure, severely restricting their reliability and shelf life. Second, conventional silicone ether defoamers rely excessively on a single mechanism of spreading and breaking foam driven by the low surface energy of siloxanes, lacking a multi-stage synergistic defoaming pathway. The rapid self-healing of the foam film results in low defoaming efficiency and insufficient foam suppression duration, making it difficult to meet the demands of continuous production for sustained foam control. Third, under high-temperature and high-shear industrial conditions, their linear molecular chain structure is prone to breakage and degradation, causing a sharp decline in foam control performance and severely limiting their applicability. Furthermore, traditional silicone ether defoamers generally rely on petroleum-based propylene oxide and mineral quartz sand-based silicone oils for preparation, resulting in non-renewable raw materials, high carbon footprints, and poor biodegradability. Therefore, it is of great significance to develop a novel silicone ether defoamer that combines green and renewable raw materials, highly stable molecular structure, rapid defoaming response, long-lasting defoaming ability, and wide adaptability to various operating conditions. Summary of the Invention
[0004] To address the above problems, the purpose of this invention is to provide a hyperbranched bio-based silicone ether composite nano defoamer and its preparation method.
[0005] To achieve the above objectives, the present invention employs the following technical solution: A hyperbranched bio-based silicone ether composite nano defoamer, by weight, comprises: 84-88 parts of star-shaped hyperbranched bio-based silicone ether copolymer, 1.5-2.5 parts of rice husk ash-derived hydrophobic nano silica, 3.0-4.5 parts of bio-wax, and 3.5-4.5 parts of bio-based emulsifier; The star-shaped hyperbranched bio-based silicone ether copolymer is prepared by covalent bonding of low-hydrogen silicone oil and hyperbranched bio-based allyl polyether via solvent-free hydrosilylation reaction; wherein the hyperbranched bio-based allyl polyether has a core of castor oil polyol and citric acid polycondensation product, grafted polyoxypropylene segments and allyl-terminated.
[0006] The bio-wax is rice bran wax or carnauba wax; the bio-based emulsifier is castor oil polyoxyethylene ether, ethoxylated hydrogenated castor oil, or castor oil phosphate.
[0007] The hyperbranched bio-based allyl polyether has a branching degree of 0.40–0.60 and a double bond content of 0.40–0.65 mmol / g; the star-shaped hyperbranched bio-based silicone ether copolymer has a residual Si–H content of no more than 0.003 wt%, a double bond conversion rate of no less than 85%, and a dynamic viscosity of 3000–6000 mPa·s at 25°C; the low-hydrogen silicone oil has a Si–H content of 0.008–0.015 wt%.
[0008] The star-shaped hyperbranched bio-based silicone ether copolymer was prepared by the following method: under nitrogen protection, low-hydrogen silicone oil and hyperbranched bio-based allyl polyether were mixed evenly, stirred at a constant speed and heated to 85-95°C, then Karstedt platinum catalyst was added, and the reaction was carried out at a constant speed for 6-8 hours. The mixture was then cooled and discharged to obtain the star-shaped hyperbranched bio-based silicone ether copolymer.
[0009] The mass ratio of the low-hydrogen silicone oil to the hyperbranched bio-based allyl polyether is 5–7:1; and the molar ratio of Si–H in the low-hydrogen silicone oil to C=C in the hyperbranched bio-based allyl polyether is 0.95–1.15:1; the amount of Karstedt platinum catalyst added is 5–10 mg / kg of the total mass of the low-hydrogen silicone oil and the hyperbranched bio-based allyl polyether.
[0010] The hyperbranched bio-based allyl polyether was prepared by the following method: hyperbranched polyol was added to a high-pressure reactor, the reactor was sealed and purged with nitrogen, the temperature was raised to 115-125°C and the pressure was maintained at 0.3-0.5 MPa, an alkaline catalyst was added, and bio-based propylene oxide was continuously introduced to carry out a ring-opening polymerization reaction for 4-6 hours; after the polymerization was completed, the pressure was released and the temperature was lowered to 75-85°C, sodium hydroxide and allyl chloride were added for end-capping etherification for 3-4 hours; after the reaction was completed, the reactor was washed with deionized water to remove salt and purified by vacuum distillation to obtain the hyperbranched bio-based allyl polyether.
[0011] The mass ratio of the hyperbranched polyol to bio-based propylene oxide is 1:3 to 8, the amount of allyl chloride is 0.15 to 0.45 times the mass of the hyperbranched polyol, and the molar ratio of sodium hydroxide to allyl chloride is 1.0 to 1.1:1; the alkaline catalyst is potassium hydroxide, potassium methoxide, potassium tert-butoxide, or a bimetallic cyanide catalyst; the amount of alkaline catalyst added is 0.1 to 0.2% of the total mass of the hyperbranched polyol and bio-based propylene oxide.
[0012] The hyperbranched polyol was prepared by the following method: castor oil polyol and citric acid were added to a reaction vessel, the vessel was sealed and vacuumed to maintain a vacuum of -0.08 to -0.09 MPa, the temperature was raised to 140 to 160°C, and the reaction was carried out by compression polymerization for 3 to 5 hours. The small molecules were removed by dehydration, and the product was cooled and discharged to obtain the hyperbranched polyol. The mass ratio of castor oil polyol to citric acid is 15~24:1.
[0013] The rice husk ash-sourced hydrophobic nano-silica was prepared according to the following method: 1) Mix rice husk ash with a 20% sodium hydroxide aqueous solution until homogeneous, stir at 90℃ for 2.5h to dissolve in alkali, filter while hot to remove carbonaceous residue and insoluble impurities; add 15% dilute hydrochloric acid to the filtrate at room temperature to adjust the pH of the system to 3.0-3.5, and a white silica precipitate will form; filter and collect the precipitate, wash repeatedly with deionized water until the pH of the filtrate is 6.8-7.2, and dry with forced air at 105℃ to obtain rice husk ash source nano-silica; The mass-to-volume ratio of the rice husk ash to the 20% sodium hydroxide aqueous solution is 1g:3~4ml; the nano-silica particles of the rice husk ash source have a particle size of 20~50nm; 2) The rice husk ash source nano-silica obtained in step 1) is uniformly dispersed in an ethanol-water mixed solution, and then vinyltrimethoxysilane is added. The mixture is stirred at a constant temperature of 55-65℃ for 2-3 hours, filtered, and dried to obtain rice husk ash source hydrophobic nano-silica. The mass ratio of ethanol to water in the ethanol-water mixture is 3-4:1; the mass ratio of rice husk ash source nano-silica, ethanol-water mixture and vinyltrimethoxysilane is 1:8-12:0.15-0.25.
[0014] The preparation method of the hyperbranched bio-based silicone ether composite nano defoamer includes the following steps: By weight, 84-88 parts of star-shaped hyperbranched bio-based silicone ether copolymer were added to a reactor and heated to 88-90°C. Then, 1.5-2.5 parts of rice husk ash-derived hydrophobic nano-silica were added and stirred for 20-30 min. Next, 3.0-4.5 parts of bio-wax and 3.5-4.5 parts of bio-based emulsifier were added. After high-speed dispersion at 1100-1400 rpm for 0.6-0.8 h, the temperature was lowered to 25-30°C at a rate of 5-8°C / min to obtain hyperbranched bio-based silicone ether composite nano-defoamer.
[0015] The present invention has the following advantages over the prior art: The hyperbranched bio-based silicone ether composite nano-defoamer of this invention abandons the traditional linear polyether structure. It utilizes castor oil polyol and citric acid through vacuum compression polymerization to construct a highly branched polyol core. This highly branched, multi-hydroxyl structure possesses numerous active reaction sites. Subsequent ring-opening polymerization with bio-based propylene oxide and allyl end-capping results in a multi-branched, multi-double-bond hyperbranched bio-based polyether. Compared to traditional linear polyethers, the hyperbranched bio-based polyether of this invention has more branches and terminal functional groups, providing multiple interfacial adsorption and reaction sites. This improves its compatibility with siloxane components, interfacial adsorption capacity, and system dispersion stability, thereby reducing the risk of stratification and oil drift during long-term storage.
[0016] The hyperbranched bio-based silicone ether composite nano defoamer of the present invention uses rice husk ash as a source of hydrophobic nano silica to prepare silica, replacing traditional non-renewable quartz minerals, while increasing the proportion of renewable raw materials used.
[0017] The hyperbranched bio-based silicone ether composite nano-defoamer of this invention utilizes a solvent-free hydrosilylation reaction to covalently bond hydrogen-containing silicone oil with hyperbranched bio-based allyl polyether, forming a three-dimensional star-shaped highly branched macromolecular structure with the hyperbranched polyether as the core and multiple siloxane chains as epitaxial branches. Unlike traditional linear silicone ether polymers, this invention naturally forms a large number of uniform nanoscale voids within the molecule, providing a stable embedding carrier for inorganic nanoparticles and achieving an integrated organic-inorganic composite rather than simple physical mixing, thus enhancing structural stability.
[0018] This invention relates to a hyperbranched bio-based silicone ether composite nano-defoamer, which uses vinyl silane to hydrophobically modify rice husk ash-derived nano-silica, improving its compatibility with the organosilicon ether matrix. The hydrophobic nano-silica particles from the rice husk ash are uniformly embedded within the star-shaped polymer nanopores. The nanoparticles rapidly pierce the foam liquid film through microscopic needle-like action, shortening the defoaming time; accelerate liquid film loss through particle bridging and drainage; and extend the defoaming period by relying on an inorganic rigid framework to hinder the self-repair of the liquid film. Simultaneously, it helps improve the system's high-temperature resistance and high-shear capacity, solving the problem of rapid performance degradation in traditional defoamers.
[0019] The hyperbranched bio-based silicone ether composite nano defoamer prepared by this invention overcomes the technical defects of existing silicone ether defoamers, such as high proportion of fossil raw materials, simple molecular structure, poor two-phase compatibility, uneven defoaming and foam suppression performance, insufficient stability under high temperature and high shear conditions, and poor biodegradability. Through multiple improvements such as bio-based raw materials, hyperbranched molecular structure, integrated covalent bonding of silicone ether, and synergistic effect of nanoparticle interstitial embedding, it achieves comprehensive technical effects such as fast defoaming speed, long foam suppression cycle, and excellent storage stability. Detailed Implementation
[0020] To better understand the technical solution of the present invention, the following detailed embodiments further illustrate the above-mentioned content of the present invention. However, this should not be construed as limiting the scope of the above-mentioned subject matter of the present invention to the following examples. All technologies implemented based on the above-mentioned content of the present invention fall within the scope of the present invention.
[0021] The castor oil polyols used in the following examples have hydroxyl values of 170–210 mg KOH / g and average functionality of 4.5–6.0; the low-hydrogen silicone oils used have Si–H content of 0.008–0.015 wt% and kinematic viscosity of 50–150 mm² / s at 25°C. The specific amount of low-hydrogen silicone oil used was determined based on its measured Si–H content and the measured double bond content of the hyperbranched bio-based allyl polyether, so that the molar ratio of Si–H to C=C was 0.95–1.15:1.
[0022] Example 1 Preparation of hyperbranched polyol: 1.5 kg castor oil polyol and 0.1 kg citric acid were added to a reaction vessel, which was sealed and vacuumed to maintain a vacuum of -0.08 MPa. The temperature was raised to 140°C, and the reaction was carried out under reduced pressure for 3 hours. The small molecules were removed by dehydration, and the product was cooled and discharged to obtain hyperbranched polyol.
[0023] Preparation of hyperbranched bio-based allyl polyether: 0.1 kg of hyperbranched polyol was added to a high-pressure reactor, sealed and purged with nitrogen, heated to 115 °C, and maintained at 0.3 MPa. 0.4 g of potassium hydroxide was added, and 0.3 kg of bio-based propylene oxide was continuously introduced to carry out ring-opening polymerization for 4 h. After polymerization, the pressure was released and the temperature was lowered to 75 °C. 8.2 g of sodium hydroxide and 0.015 kg of allyl chloride were added for end-capping for 3 h. After the reaction, the product was washed with deionized water to remove salt and purified by vacuum distillation to obtain hyperbranched bio-based allyl polyether.
[0024] Preparation of star-shaped hyperbranched bio-based silicone ether copolymer: Under nitrogen protection, 0.5 kg of low-hydrogen silicone oil and 0.1 kg of hyperbranched bio-based allyl polyether were mixed evenly, stirred at a constant speed and heated to 85 °C, and then 3 mg of Karstedt platinum catalyst was added. The mixture was kept at the temperature and stirred at a constant speed for 6 h, cooled and discharged to obtain star-shaped hyperbranched bio-based silicone ether copolymer.
[0025] Preparation of hydrophobic nano-silica from rice husk ash: 1) Mix 1 kg of rice husk ash with 3 L of 20% sodium hydroxide aqueous solution, stir at 90℃ for 2.5 h to dissolve in alkali, filter while hot to remove carbon residue and insoluble impurities; add 15% hydrochloric acid dropwise to the filtrate at room temperature to adjust the pH of the system to 3.0, and a white precipitate of silica will precipitate; filter and collect the precipitate, wash repeatedly with deionized water until the pH of the filtrate is 6.8, and dry with forced air at 105℃ to obtain rice husk ash source nano-silica; 2) 0.1 kg of rice husk ash source nano-silica was uniformly dispersed in 0.8 kg of ethanol-water mixed solution, wherein the mass ratio of ethanol to water was 3:1. Then 0.015 kg of vinyltrimethoxysilane was added, and the mixture was stirred at 55 °C for 2 h for modification. After filtration and drying, hydrophobic nano-silica source of rice husk ash was obtained.
[0026] Preparation of hyperbranched bio-based silicone ether composite nano defoamer: 0.84 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 88°C. Then, 0.015 kg of rice husk ash-derived hydrophobic nano-silica was added and stirred for 20 min. Next, 0.03 kg of rice bran wax and 0.035 kg of castor oil polyoxyethylene ether were added. After high-speed dispersion at 1100 rpm for 0.6 h, the temperature was lowered to 25°C at a rate of 5°C / min to obtain the hyperbranched bio-based silicone ether composite nano-defoamer.
[0027] Example 2 Preparation of hyperbranched polyol: 1.7 kg castor oil polyol and 0.1 kg citric acid were added to a reaction vessel, which was sealed and vacuumed to maintain a vacuum of -0.09 MPa. The temperature was raised to 145°C, and the reaction was carried out under reduced pressure for 3.5 h. The small molecules were removed by dehydration, and the product was cooled and discharged to obtain hyperbranched polyol.
[0028] Preparation of hyperbranched bio-based allyl polyether: 0.1 kg of hyperbranched polyol was added to a high-pressure reactor, sealed and purged with nitrogen, heated to 120 °C, and maintained at 0.4 MPa. 0.6 g of potassium methoxide was added, and 0.4 kg of bio-based propylene oxide was continuously introduced to carry out ring-opening polymerization for 4.5 h. After polymerization, the pressure was released and the temperature was lowered to 75 °C. 11.0 g of sodium hydroxide and 0.02 kg of allyl chloride were added for end-capping etherification for 3.2 h. After the reaction, the product was washed with deionized water to remove salt and purified by vacuum distillation to obtain hyperbranched bio-based allyl polyether.
[0029] Preparation of star-shaped hyperbranched bio-based silicone ether copolymer: Under nitrogen protection, 0.53 kg of low-hydrogen silicone oil and 0.1 kg of hyperbranched bio-based allyl polyether were mixed evenly and stirred at a constant speed to raise the temperature to 88°C. Then, 3.8 mg of Karstedt platinum catalyst was added, and the reaction was carried out at a constant temperature and stirred at a constant speed for 6.5 h. The mixture was then cooled and discharged to obtain the star-shaped hyperbranched bio-based silicone ether copolymer.
[0030] Preparation of hydrophobic nano-silica from rice husk ash: 1) Mix 1 kg of rice husk ash with 3.2 L of 20% sodium hydroxide aqueous solution, stir at 90℃ for 2.5 h to dissolve in alkali, filter while hot to remove carbonaceous residue and insoluble impurities; add 15% hydrochloric acid dropwise to the filtrate at room temperature to adjust the pH of the system to 3.1, and a white precipitate of silica will precipitate; filter and collect the precipitate, wash repeatedly with deionized water until the pH of the filtrate is 6.9, and dry with forced air at 105℃ to obtain rice husk ash source nano-silica; 2) 0.1 kg of rice husk ash source nano-silica was uniformly dispersed in 0.9 kg of ethanol-water mixed solution, wherein the mass ratio of ethanol to water was 3.2:1. Then 0.018 kg of vinyltrimethoxysilane was added, and the mixture was stirred at 58 °C for 2.3 h for modification. After filtration and drying, hydrophobic nano-silica source of rice husk ash was obtained.
[0031] Preparation of hyperbranched bio-based silicone ether composite nano defoamer: 0.85 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 89°C. Then, 0.017 kg of rice husk ash-derived hydrophobic nano-silica was added and stirred for 21 min. Next, 0.033 kg of carnauba wax and 0.037 kg of ethoxylated hydrogenated castor oil were added. After high-speed dispersion at 1200 rpm for 0.65 h, the temperature was lowered to 26°C at a rate of 6°C / min to obtain the hyperbranched bio-based silicone ether composite nano-defoamer.
[0032] Example 3 Preparation of hyperbranched polyol: 2 kg of castor oil polyol and 0.1 kg of citric acid were added to a reaction vessel, which was sealed and vacuumed to maintain a vacuum of -0.08 MPa. The temperature was raised to 150°C, and the reaction was carried out under reduced pressure for 4 hours. The small molecules were removed by dehydration, and the product was cooled and discharged to obtain hyperbranched polyol.
[0033] The hydroxyl value of the hyperbranched polyol was determined according to the method specified in GB / T 7383—2020 "Determination of Hydroxyl Value of Nonionic Surfactants". The determination was performed in parallel for 3 times and the arithmetic mean of the results was taken. The hydroxyl value was 188 mg KOH / g.
[0034] The acid value was determined according to the method specified in GB / T 12008.5—2010 "Plastic Polyether Polyols Part 5: Determination of Acid Value". The determination was performed in parallel for three times, and the arithmetic mean of the results was taken. The acid value was 9.6 mg KOH / g.
[0035] The degree of branching was determined by quantitative carbon-13 nuclear magnetic resonance spectroscopy: the sample was dissolved in deuterated dimethyl sulfoxide, and ¹³C NMR spectra were acquired using a reverse-gated proton decoupling method. Based on the integral area of the characteristic carbon signals of the end-unit, linear, and branched structural units, the contents of the end-unit, linear, and branched units were obtained, respectively. The degree of branching of the hyperbranched polyol was calculated to be 0.48.
[0036] The number-average molecular weight (Mn) was determined by gel permeation chromatography using tetrahydrofuran as the mobile phase. The detection conditions followed GB / T 21863—2008, "Gel Permeation Chromatography (GPC) - Using Tetrahydrofuran as Eluent". The average hydroxyl functionality was calculated based on the measured number-average molecular weight and hydroxyl value using the following formula. The calculated average hydroxyl functionality of the hyperbranched polyol was 5.2.
[0037] Preparation of hyperbranched bio-based allyl polyether: 0.1 kg of hyperbranched polyol was added to a high-pressure reactor, sealed and purged with nitrogen, heated to 121 °C, and maintained at 0.35 MPa. 0.9 g of potassium tert-butoxide was added, and 0.5 kg of bio-based propylene oxide was continuously introduced to carry out ring-opening polymerization for 5 h. After polymerization, the pressure was released and the temperature was lowered to 80 °C. 13.7 g of sodium hydroxide and 0.025 kg of allyl chloride were added for end-capping etherification for 3.5 h. After the reaction, the product was washed with deionized water to remove salt and purified by vacuum distillation to obtain hyperbranched bio-based allyl polyether.
[0038] The double bond content of the hyperbranched bio-based allyl polyether was determined according to GB / T 12008.6—2010 "Plastic Polyether Polyols Part 6: Determination of Unsaturation". The determination was performed in triplicate, and the arithmetic mean of the results was taken. The double bond content was found to be 0.52 mmol / g.
[0039] The allyl structure was verified by ¹H NMR. Characteristic peaks of the terminal double bond proton (CH2 in —CH=CH2) of the allyl group were observed in the range of 5.15–5.35 ppm, and characteristic peaks of the allyl methine proton (CH in —CH=CH2) were observed in the range of 5.85–5.95 ppm.
[0040] The hydroxyl value of the hyperbranched bio-based allyl polyether was determined according to the method specified in GB / T 7383-2020 "Nonionic Surfactants - Determination of Hydroxyl Value". The determination was performed in parallel for 3 times and the arithmetic mean of the results was taken. The hydroxyl value was 18.6 mgKOH / g. The relative molecular mass and its distribution were determined by gel permeation chromatography with tetrahydrofuran as the mobile phase. The number-average molecular weight (Mn) was 4100 g / mol, the weight-average molecular weight (Mw) was 5660 g / mol, and the dispersion index was 1.38.
[0041] Preparation of star-shaped hyperbranched bio-based silicone ether copolymer: The Si–H content of the low-hydrogen silicone oil used was determined to be 0.0097 wt% by the alcoholysis gasification method. Based on the measured Si–H content of the low-hydrogen silicone oil and the measured double bond content of 0.52 mmol / g of the hyperbranched bio-based allyl polyether, the molar ratio of Si–H in the low-hydrogen silicone oil to C=C in the hyperbranched bio-based allyl polyether was approximately 1.08:1. Under nitrogen protection, 0.58 kg of the low-hydrogen silicone oil and 0.1 kg of the hyperbranched bio-based allyl polyether were mixed evenly, stirred at a constant speed, and heated to 90 °C. Then, 4.8 mg of Karstedt platinum catalyst was added, and the reaction was maintained at this temperature with constant stirring for 7 h. After cooling, the product was discharged to obtain the star-shaped hyperbranched bio-based silicone ether copolymer.
[0042] The residual Si–H content of the reaction products was determined using the alcoholysis gasification method. Based on the mass fraction of active hydrogen contained in the Si–H bonds, the residual Si–H content was found to be 0.0015 wt%. 1 The content of allyl double bonds before and after the reaction was determined by H NMR internal standard integration method, and the double bond conversion rate was calculated to be 88.4%. The above results indicate that Si–H in low-hydrogen silicone oil underwent a hydrosilylation reaction with the allyl double bonds in hyperbranched bio-based allyl polyether, and a small amount of unreacted Si–H was retained.
[0043] Referring to GB / T 21863—2008 "Gel Permeation Chromatography (GPC) with Tetrahydrofuran as Eluent", the relative molecular mass and its distribution were determined using a gel permeation chromatograph. Tetrahydrofuran was used as the mobile phase, monodisperse polystyrene was used as the calibration standard, and a differential refractive index detector was used for detection. The relative number-average molecular weight (Mn) was 14800 g / mol, the relative weight-average molecular weight (Mw) was 25900 g / mol, and the dispersion index was 1.75.
[0044] According to GB / T 12008.7—2010 "Plastics Polyether Polyols Part 7: Determination of Viscosity", the dynamic viscosity at 25℃ was measured using a rotational viscometer, and the dynamic viscosity was found to be 4250 mPa·s.
[0045] Fourier transform infrared spectroscopy analysis was performed according to GB / T 6040—2019 "General Rules for Infrared Spectroscopic Analysis Methods". The image was taken at approximately 1260 cm⁻¹. -1 The absorption peak of Si—CH3 was used as an internal standard peak at approximately 2160 cm⁻¹. -1 After normalization of the Si–H stretching vibration peak, the value was approximately 2160 cm⁻¹. -1The Si–H normalized absorption peak was significantly weakened, indicating that Si–H participated in the hydrosilylation reaction. In the ¹H NMR spectrum, the allyl matrix sub-peaks at δ5.15–5.35 ppm and δ5.85–5.95 ppm were significantly weakened, and their normalized integral area decreased by about 88% compared with that before the reaction, which is basically consistent with the double bond conversion detection results.
[0046] Preparation of hydrophobic nano-silica from rice husk ash: 1) Mix 1 kg of rice husk ash with 3.4 L of 20% sodium hydroxide aqueous solution, stir at 90 °C for 2.5 h to dissolve in alkali, filter while hot to remove carbonaceous residue and insoluble impurities; add 15% hydrochloric acid dropwise to the filtrate at room temperature to adjust the pH of the system to 3.2, and a white precipitate of silica will precipitate; filter and collect the precipitate, wash repeatedly with deionized water until the pH of the filtrate is 7, and dry with forced air at 105 °C to obtain rice husk ash source nano-silica; 2) 0.1 kg of rice husk ash source nano-silica was uniformly dispersed in 1 kg of ethanol-water mixed solution, wherein the mass ratio of ethanol to water was 3.4:1. Then 0.02 kg of vinyltrimethoxysilane was added, and the mixture was stirred at 60℃ for 2.5 h for modification. After filtration and drying, hydrophobic nano-silica source of rice husk ash was obtained.
[0047] The elemental composition of the unmodified rice husk ash-based nano-silica was determined by X-ray fluorescence spectroscopy, and the purity of SiO2 was found to be 98.1% based on the calcined inorganic components.
[0048] The equivalent hydrodynamic particle size distribution of hydrophobic nano-silica from rice husk ash source was determined according to GB / T 29022—2021 "Particle size analysis by dynamic light scattering (DLS)". The D10, D50 and D90 were 20 nm, 34 nm and 49 nm, respectively.
[0049] Rice husk ash-based nano-silica and rice husk ash-based hydrophobic nano-silica were pressed into smooth circular discs under the same pressure, and the apparent water contact angle was measured using the seat drop method. Measurements were taken at least five different locations for each sample, and the average value was calculated. The measured apparent water contact angle was 28° for rice husk ash-based nano-silica and 118° for rice husk ash-based hydrophobic nano-silica. The contact angle results indicate that the surface hydrophobicity of rice husk ash-based hydrophobic nano-silica is significantly enhanced.
[0050] Fourier transform infrared spectroscopy analysis was performed according to GB / T 6040—2019 "General Rules for Infrared Spectroscopic Analysis Methods". Compared with rice husk ash-based nano-silica, rice husk ash-based hydrophobic nano-silica exhibits better performance at approximately 1600 cm⁻¹. -1 The presence of a vinyl C=C stretching vibration absorption peak indicates that vinyl silane has been introduced into the silica surface.
[0051] Thermogravimetric analysis was performed according to GB / T 33047.1—2025 "Plastic Polymers - Thermogravimetric Analysis (TG) - Part 1: General Rules". The mass loss of rice husk ash-derived nano-silica and rice husk ash-derived hydrophobic nano-silica was measured under the same heating program. After deducting the mass loss due to dehydroxylation of the rice husk ash-derived nano-silica, the surface organic modification amount of the rice husk ash-derived hydrophobic nano-silica was calculated to be 2.3%.
[0052] Preparation of hyperbranched bio-based silicone ether composite nano defoamer: 0.86 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 89°C. Then, 0.02 kg of rice husk ash-derived hydrophobic nano-silica was added and stirred for 24 min. Next, 0.04 kg of carnauba wax and 0.04 kg of castor oil polyoxyethylene ether were added. After high-speed dispersion at 1200 rpm for 0.7 h, the temperature was lowered to 28°C at a rate of 7°C / min to obtain the hyperbranched bio-based silicone ether composite nano-defoamer.
[0053] Example 4 Preparation of hyperbranched polyol: 2.1 kg castor oil polyol and 0.1 kg citric acid were added to a reaction vessel, which was sealed and vacuumed to maintain a vacuum of -0.09 MPa. The temperature was raised to 155°C, and the reaction was carried out under reduced pressure for 4.5 h. The small molecules were removed by dehydration, and the product was cooled and discharged to obtain hyperbranched polyol.
[0054] Preparation of hyperbranched bio-based allyl polyether: 0.1 kg of hyperbranched polyol was added to a high-pressure reactor, sealed and purged with nitrogen, heated to 122 °C, and maintained at 0.45 MPa. 1.05 g of potassium tert-butoxide was added, and 0.6 kg of bio-based propylene oxide was continuously introduced to carry out ring-opening polymerization for 5.5 h. After polymerization, the pressure was released and the temperature was lowered to 82 °C. 16.5 g of sodium hydroxide and 0.03 kg of allyl chloride were added for end-capping etherification for 3.6 h. After the reaction, the product was washed with deionized water for desalting and purified by vacuum distillation to obtain hyperbranched bio-based allyl polyether.
[0055] Preparation of star-shaped hyperbranched bio-based silicone ether copolymer: Under nitrogen protection, 0.64 kg of low-hydrogen silicone oil and 0.1 kg of hyperbranched bio-based allyl polyether were mixed evenly and stirred at a constant speed to 91 °C. Then, 5.9 mg of Karstedt platinum catalyst was added, and the mixture was kept at the temperature and stirred at a constant speed for 7.4 h. The mixture was then cooled and discharged to obtain the star-shaped hyperbranched bio-based silicone ether copolymer.
[0056] Preparation of hydrophobic nano-silica from rice husk ash: 1) Mix 1 kg of rice husk ash with 3.5 L of 20% sodium hydroxide aqueous solution, stir at 90 °C for 2.5 h to dissolve in alkali, filter while hot to remove carbonaceous residue and insoluble impurities; add 15% hydrochloric acid dropwise to the filtrate at room temperature to adjust the pH of the system to 3.3, and a white precipitate of silica will precipitate; filter and collect the precipitate, wash repeatedly with deionized water until the pH of the filtrate is 7.1, and dry with forced air at 105 °C to obtain rice husk ash source nano-silica; 2) 0.1 kg of rice husk ash source nano-silica was uniformly dispersed in 1.1 kg of ethanol-water mixed solution, wherein the mass ratio of ethanol to water was 3.6:1. Then 0.021 kg of vinyltrimethoxysilane was added, and the mixture was stirred at 62℃ for 2.6 h for modification. After filtration and drying, hydrophobic nano-silica source of rice husk ash was obtained.
[0057] Preparation of hyperbranched bio-based silicone ether composite nano defoamer: 0.87 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 89 °C. Then, 0.023 kg of hydrophobic nano-silica from rice husk ash was added and stirred for 27 min. Next, 0.041 kg of rice bran wax and 0.042 kg of castor oil phosphate were added. After high-speed dispersion at 1300 rpm for 0.7 h, the temperature was lowered to 29 °C at a rate of 7.5 °C / min to obtain hyperbranched bio-based silicone ether composite nano-defoamer.
[0058] Example 5 Preparation of hyperbranched polyol: 2.3 kg castor oil polyol and 0.1 kg citric acid were added to a reaction vessel, which was sealed and vacuumed to maintain a vacuum of -0.09 MPa. The temperature was raised to 150°C, and the reaction was carried out under reduced pressure for 4 hours. The small molecules were removed by dehydration, and the product was cooled and discharged to obtain hyperbranched polyol.
[0059] Preparation of hyperbranched bio-based allyl polyether: 0.1 kg of hyperbranched polyol was added to a high-pressure reactor, sealed and purged with nitrogen, heated to 124 °C, and maintained at 0.48 MPa. 1.44 g of potassium methoxide was added, and 0.7 kg of bio-based propylene oxide was continuously introduced to carry out ring-opening polymerization for 5 h. After polymerization, the pressure was released and the temperature was lowered to 80 °C. 22.0 g of sodium hydroxide and 0.04 kg of allyl chloride were added for end-capping etherification for 3.8 h. After the reaction, the product was washed with deionized water for desalting and purified by vacuum distillation to obtain hyperbranched bio-based allyl polyether.
[0060] Preparation of star-shaped hyperbranched bio-based silicone ether copolymer: Under nitrogen protection, 0.65 kg of low-hydrogen silicone oil and 0.1 kg of hyperbranched bio-based allyl polyether were mixed evenly and stirred at a constant speed to 93 °C. Then, 6.4 mg of Karstedt platinum catalyst was added, and the mixture was kept at the temperature and stirred at a constant speed for 7.7 h. The mixture was then cooled and discharged to obtain the star-shaped hyperbranched bio-based silicone ether copolymer.
[0061] Preparation of hydrophobic nano-silica from rice husk ash: 1) Mix 1 kg of rice husk ash with 3.9 L of 20% sodium hydroxide aqueous solution, stir at 90℃ for 2.5 h to dissolve in alkali, filter while hot to remove carbon residue and insoluble impurities; add 15% hydrochloric acid dropwise to the filtrate at room temperature to adjust the pH of the system to 3.4, and a white precipitate of silica will be precipitated; filter and collect the precipitate, wash repeatedly with deionized water until the pH of the filtrate is 7.1, and dry with forced air at 105℃ to obtain rice husk ash source nano-silica; 2) 0.1 kg of rice husk ash source nano-silica was uniformly dispersed in 1.1 kg of ethanol-water mixed solution, wherein the mass ratio of ethanol to water was 3.8:1. Then 0.023 kg of vinyltrimethoxysilane was added, and the mixture was stirred at 64℃ for 2.8 h for modification. After filtration and drying, hydrophobic nano-silica source of rice husk ash was obtained.
[0062] Preparation of hyperbranched bio-based silicone ether composite nano defoamer: 0.87 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 90 °C. Then, 0.024 kg of hydrophobic nano-silica from rice husk ash was added and stirred for 29 min. Next, 0.044 kg of rice bran wax and 0.044 kg of ethoxylated hydrogenated castor oil were added. After high-speed dispersion at 1400 rpm for 0.7 h, the temperature was lowered to 26 °C at a rate of 7.5 °C / min to obtain hyperbranched bio-based silicone ether composite nano-defoamer.
[0063] Example 6 Preparation of hyperbranched polyol: 2.4 kg castor oil polyol and 0.1 kg citric acid were added to a reaction vessel, which was sealed and vacuumed to maintain a vacuum of -0.09 MPa. The temperature was raised to 160°C, and the reaction was carried out under reduced pressure for 5 h. After dehydration and removal of small molecules, the product was cooled and discharged to obtain hyperbranched polyol.
[0064] Preparation of hyperbranched bio-based allyl polyether: 0.1 kg of hyperbranched polyol was added to a high-pressure reactor, sealed and purged with nitrogen, heated to 125 °C, and maintained at 0.5 MPa. 1.8 g of bimetallic cyanide catalyst was added, and 0.8 kg of bio-based propylene oxide was continuously introduced to carry out ring-opening polymerization for 6 h. After polymerization, the pressure was released and the temperature was lowered to 85 °C. 24.7 g of sodium hydroxide and 0.045 kg of allyl chloride were added for end-capping etherification for 4 h. After the reaction, the product was washed with deionized water for desalting and purified by vacuum distillation to obtain hyperbranched bio-based allyl polyether.
[0065] Preparation of star-shaped hyperbranched bio-based silicone ether copolymer: Under nitrogen protection, 0.7 kg of low-hydrogen silicone oil and 0.1 kg of hyperbranched bio-based allyl polyether were mixed evenly, stirred at a constant speed and heated to 95 °C, and then 8 mg of Karstedt platinum catalyst was added. The mixture was kept at the temperature and stirred at a constant speed for 8 h, cooled and discharged to obtain star-shaped hyperbranched bio-based silicone ether copolymer.
[0066] Preparation of hydrophobic nano-silica from rice husk ash: 1) Mix 1 kg of rice husk ash with 4 L of 20% sodium hydroxide aqueous solution, stir at 90℃ for 2.5 h to dissolve in alkali, filter while hot to remove carbon residue and insoluble impurities; add 15% hydrochloric acid dropwise to the filtrate at room temperature to adjust the pH of the system to 3.5, and a white precipitate of silica will be precipitated; filter and collect the precipitate, wash repeatedly with deionized water until the pH of the filtrate is 7.2, and dry with forced air at 105℃ to obtain rice husk ash source nano-silica; 2) Disperse 0.1 kg of rice husk ash source nano-silica in 1.2 kg of ethanol-water mixed solution, wherein the mass ratio of ethanol to water is 4:1, and then add 0.025 kg of vinyltrimethoxysilane. The mixture is stirred at 65℃ for 3 h for modification, filtered, and dried to obtain rice husk ash source hydrophobic nano-silica.
[0067] Preparation of hyperbranched bio-based silicone ether composite nano defoamer: 0.88 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 90°C. Then, 0.025 kg of hydrophobic nano-silica from rice husk ash was added and stirred for 30 min. Next, 0.045 kg of rice bran wax and 0.045 kg of ethoxylated hydrogenated castor oil were added. After high-speed dispersion at 1400 rpm for 0.8 h, the temperature was lowered to 30°C at a rate of 8°C / min to obtain the hyperbranched bio-based silicone ether composite nano-defoamer.
[0068] Comparative Example 1: This comparative example is prepared using the same method as Example 3, except for the preparation of the hyperbranched bio-based silicone ether composite nano-defoamer. 0.86 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 89°C. Then, 0.005 kg of rice husk ash-derived hydrophobic nano-silica was added and stirred for 24 min. Next, 0.04 kg of carnauba wax and 0.04 kg of castor oil polyoxyethylene ether were added. After high-speed dispersion at 1200 rpm for 0.7 h, the temperature was lowered to 28°C at a rate of 7°C / min to obtain the hyperbranched bio-based silicone ether composite nano-defoamer.
[0069] Comparative Example 2: This comparative example was prepared using the same method as Example 3, except for the preparation of the hyperbranched bio-based silicone ether composite nano-defoamer. 0.86 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 89°C. Then, 0.04 kg of rice husk ash-derived hydrophobic nano-silica was added and stirred for 24 min. Next, 0.04 kg of carnauba wax and 0.04 kg of castor oil polyoxyethylene ether were added. After high-speed dispersion at 1200 rpm for 0.7 h, the temperature was lowered to 28°C at a rate of 7°C / min to obtain the hyperbranched bio-based silicone ether composite nano-defoamer.
[0070] Comparative Example 3: This comparative example is prepared using the same method as Example 3, except for the preparation of the hyperbranched bio-based silicone ether composite nano-defoamer. 0.86 kg of linear allyl polyether was added to the reactor and heated to 89 °C. Then, 0.02 kg of hydrophobic nano-silica derived from rice husk ash was added and stirred for 24 min. Next, 0.04 kg of carnauba wax and 0.04 kg of castor oil polyoxyethylene ether were added. After high-speed dispersion at 1200 rpm for 0.7 h, the temperature was lowered to 28 °C at a rate of 7 °C / min to obtain hyperbranched bio-based silicone ether composite nano-defoamer.
[0071] Comparative Example 4: This comparative example was prepared using the same method as Example 3, except for the preparation of the hyperbranched bio-based silicone ether composite nano-defoamer. 0.58 kg of low-hydrogen silicone oil and 0.1 kg of hyperbranched bio-based allyl polyether were mixed evenly and added to a reactor. The mixture was heated to 89°C, and then 0.02 kg of hydrophobic nano-silica from rice husk ash was added. After stirring for 24 min, 0.04 kg of carnauba wax and 0.04 kg of castor oil polyoxyethylene ether were added. The mixture was dispersed at high speed at 1200 rpm for 0.7 h, and then cooled to 28°C at a rate of 7°C / min to obtain a hyperbranched bio-based silicone ether composite nano-defoamer.
[0072] Comparative Example 5: This comparative example was prepared using the same method as Example 3, except for the preparation of the hyperbranched bio-based silicone ether composite nano-defoamer. 0.86 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 89°C. Then, 0.02 kg of rice husk ash-based nano-silica was added and stirred for 24 min. Next, 0.04 kg of carnauba wax and 0.04 kg of castor oil polyoxyethylene ether were added. After high-speed dispersion at 1200 rpm for 0.7 h, the temperature was lowered to 28°C at a rate of 7°C / min to obtain the hyperbranched bio-based silicone ether composite nano-defoamer.
[0073] Comparative Example 6: This comparative example was prepared using the same method as Example 3, except for the preparation of the hyperbranched bio-based silicone ether composite nano-defoamer. 0.86 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor, heated to 89 °C, and stirred for 24 min. Then, 0.04 kg of carnauba wax and 0.04 kg of castor oil polyoxyethylene ether were added. After high-speed dispersion at 1200 rpm for 0.7 h, the temperature was lowered to 28 °C at a rate of 7 °C / min to obtain hyperbranched bio-based silicone ether composite nano defoamer.
[0074] Comparative Example 7: This comparative example was prepared using the same method as Example 3, except for the preparation of the hyperbranched bio-based silicone ether composite nano-defoamer. 0.86 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 89°C. Then, 0.02 kg of hydrophobic nano-silica was added and stirred for 24 min. Next, 0.04 kg of carnauba wax and 0.04 kg of castor oil polyoxyethylene ether were added. After high-speed dispersion at 1200 rpm for 0.7 h, the temperature was lowered to 28°C at a rate of 7°C / min to obtain the hyperbranched bio-based silicone ether composite nano-defoamer. The hydrophobic nano-silica was prepared by direct hydrophobic modification of commercially available nano-silica.
[0075] Comparative Example 8: This comparative example was prepared using the same method as Example 3, except for the preparation of the hyperbranched bio-based silicone ether composite nano-defoamer. 0.86 kg of star-shaped hyperbranched bio-based silicone ether copolymer was added to a reactor and heated to 89°C. Then, 0.02 kg of rice husk ash-derived hydrophobic nano-silica was added and stirred for 24 min. Finally, 0.04 kg of castor oil polyoxyethylene ether was added. After high-speed dispersion at 1200 rpm for 0.7 h, the temperature was lowered to 28°C at a rate of 7°C / min to obtain the hyperbranched bio-based silicone ether composite nano-defoamer.
[0076] The differences in parameter settings between Comparative Examples 1-8 and Example 3 are shown in Table 1.
[0077] Table 1. Differences in parameter settings between Comparative Examples 1-8 and Example 3
[0078] The products prepared in Examples 1-6 and Comparative Examples 1-8 were subjected to performance tests, and the test methods are as follows: (1) Defoaming and foam suppression: 100 mL of 5% sodium dodecylbenzenesulfonate aqueous solution was placed in a 500 mL graduated cylinder and bubbled for 3 min at 25±1℃. Air was used as the bubbling gas and the foam was bubbled at a constant flow rate of 100 mL / min for 3 min until the total foam volume reached 500 mL. 0.1% of the foaming medium mass of defoamer was added. The time required for the total foam volume to drop to 100 mL was recorded as the defoaming time, and the time required for the total foam volume to rise back to 500 mL was recorded as the foam suppression time.
[0079] (2) High shear retention rate: The sample was sheared at 3000 r / min for 30 min at 25℃, and the foam suppression time after shearing was measured in the same way. The foam suppression time after shearing was calculated as the ratio of the foam suppression time before shearing to the foam suppression time before shearing.
[0080] (3) Storage stability: The samples were placed in a sealed container at 50℃ for 30 days and 90 days. After being restored to room temperature, the separation, oil floating, sedimentation and thickening were observed. The test results are shown in Table 2.
[0081] Table 2 Performance test results of the examples and comparative examples
[0082] As shown in Table 2, the hyperbranched bio-based silicone ether composite nano defoamer prepared by the method of the present invention has a shorter defoaming time, a longer foam suppression time, and a higher shear retention rate. When the amount of nano silica is lower than the lower limit, the synergistic foam suppression effect weakens, and when the amount is higher than the upper limit, the particle size may increase and the storage stability may decrease due to agglomeration.
[0083] Compared with Comparative Examples 3 and 4, Example 3 showed that the defoaming time was shortened by approximately 38.0% and 46.0%, respectively, and the foam suppression time was increased by approximately 53.3% and 74.1%, respectively. This indicates that the hyperbranched topology and the covalent framework formed by hydrosilylation jointly improved the rapid defoaming, sustained foam suppression, and high shear stability.
[0084] Compared with Comparative Example 5, Example 3 showed that the defoaming time was shortened by about 30.2%, the foam suppression time was increased by about 39.6%, and the storage state was improved from sedimentation to uniformity, indicating that hydrophobic modification of rice husk ash source silica is beneficial to its dispersion and interfacial compatibility in the silyl ether matrix.
[0085] Compared with Comparative Example 6, Example 3 showed an increase of approximately 45.4% in foam suppression time, indicating that nano-silica has a significant contribution to sustained foam suppression. Comparative Example 6 had a smaller particle size but lower overall performance, which also shows that particle size is not the only determining factor.
[0086] The main performance of Example 3 is similar to that of Comparative Example 7, indicating that under the same hydrophobic modification conditions, the rice husk ash source itself does not show any performance disadvantage, and its main value lies in realizing the reuse of silicon resources.
[0087] Compared with Comparative Example 8, Example 3 showed a reduction of approximately 20.2% in defoaming time, an increase of approximately 22.6% in foam suppression time, and greater stability during long-term storage, indicating that biowax has a synergistic effect on rapid defoaming, sustained foam suppression, and system stability.
[0088] While the specific embodiments of the present invention have been described above, they are not intended to limit the scope of protection of the present invention. Based on the technical solutions of the present invention, various modifications or variations that can be made by those skilled in the art without creative effort are still within the scope of protection of the present invention.
Claims
1. A hyperbranched bio-based silicone ether composite nano defoamer, characterized in that: By weight, it comprises: 84-88 parts of star-shaped hyperbranched bio-based silicone ether copolymer, 1.5-2.5 parts of rice husk ash-derived hydrophobic nano-silica, 3.0-4.5 parts of bio-wax, and 3.5-4.5 parts of bio-based emulsifier; The star-shaped hyperbranched bio-based silicone ether copolymer is prepared by covalent bonding of low-hydrogen silicone oil and hyperbranched bio-based allyl polyether via solvent-free hydrosilylation reaction; wherein the hyperbranched bio-based allyl polyether has a core of hyperbranched polyol, a polycondensation product of castor oil polyol and citric acid, grafted with polyoxypropylene segments and allyl-terminated.
2. The hyperbranched bio-based silicone ether composite nano defoamer as described in claim 1, characterized in that: The bio-wax is rice bran wax or carnauba wax; the bio-based emulsifier is castor oil polyoxyethylene ether, ethoxylated hydrogenated castor oil, or castor oil phosphate.
3. The hyperbranched bio-based silicone ether composite nano defoamer as described in claim 1, characterized in that: The hyperbranched bio-based allyl polyether has a branching degree of 0.40–0.60 and a double bond content of 0.40–0.65 mmol / g; the star-shaped hyperbranched bio-based silicone ether copolymer has a residual Si–H content of no more than 0.003 wt%, a double bond conversion rate of no less than 85%, and a dynamic viscosity of 3000–6000 mPa·s at 25°C; the low-hydrogen silicone oil has a Si–H content of 0.008–0.015 wt%.
4. The hyperbranched bio-based silicone ether composite nano defoamer as described in claim 3, characterized in that: The star-shaped hyperbranched bio-based silicone ether copolymer was prepared by the following method: under nitrogen protection, low-hydrogen silicone oil and hyperbranched bio-based allyl polyether were mixed evenly, stirred at a constant speed and heated to 85-95°C, then Karstedt platinum catalyst was added, and the reaction was carried out at a constant speed for 6-8 hours. The mixture was then cooled and discharged to obtain the star-shaped hyperbranched bio-based silicone ether copolymer.
5. The hyperbranched bio-based silicone ether composite nano defoamer as described in claim 4, characterized in that: The mass ratio of the low-hydrogen silicone oil to the hyperbranched bio-based allyl polyether is 5-7:1, and the molar ratio of Si–H in the low-hydrogen silicone oil to C=C in the hyperbranched bio-based allyl polyether is 0.95-1.15:1; the amount of Karstedt platinum catalyst added is 5-10 mg / kg of the total mass of the low-hydrogen silicone oil and the hyperbranched bio-based allyl polyether.
6. The hyperbranched bio-based silicone ether composite nano defoamer as described in claim 4, characterized in that: The hyperbranched bio-based allyl polyether was prepared by the following method: hyperbranched polyol was added to a high-pressure reactor, the reactor was sealed and purged with nitrogen, the temperature was raised to 115-125°C and the pressure was maintained at 0.3-0.5 MPa, an alkaline catalyst was added, and bio-based propylene oxide was continuously introduced to carry out a ring-opening polymerization reaction for 4-6 hours; after the polymerization was completed, the pressure was released and the temperature was lowered to 75-85°C, sodium hydroxide and allyl chloride were added for end-capping etherification for 3-4 hours; after the reaction was completed, the reactor was washed with deionized water to remove salt and purified by vacuum distillation to obtain the hyperbranched bio-based allyl polyether.
7. The hyperbranched bio-based silicone ether composite nano defoamer as described in claim 6, characterized in that: The mass ratio of the hyperbranched polyol to bio-based propylene oxide is 1:3 to 8, the amount of allyl chloride is 0.15 to 0.45 times the mass of the hyperbranched polyol, and the molar ratio of sodium hydroxide to allyl chloride is 1.0 to 1.1:1; the alkaline catalyst is potassium hydroxide, potassium methoxide, potassium tert-butoxide, or a bimetallic cyanide catalyst; the amount of alkaline catalyst added is 0.1 to 0.2% of the total mass of the hyperbranched polyol and bio-based propylene oxide.
8. The hyperbranched bio-based silicone ether composite nano defoamer as described in claim 6, characterized in that: The hyperbranched polyol was prepared by the following method: castor oil polyol and citric acid were added to a reaction vessel, the vessel was sealed and vacuumed to maintain a vacuum of -0.08 to -0.09 MPa, the temperature was raised to 140 to 160°C, and the reaction was carried out by compression polymerization for 3 to 5 hours. The small molecules were removed by dehydration, and the product was cooled and discharged to obtain the hyperbranched polyol. The mass ratio of castor oil polyol to citric acid is 15~24:
1.
9. The hyperbranched bio-based silicone ether composite nano defoamer as described in claim 1, characterized in that: The rice husk ash-sourced hydrophobic nano-silica was prepared according to the following method: 1) Mix rice husk ash with a 20% sodium hydroxide aqueous solution until homogeneous, stir at 90℃ for 2.5h to dissolve in alkali, filter while hot to remove carbonaceous residue and insoluble impurities; add 15% dilute hydrochloric acid to the filtrate at room temperature to adjust the pH of the system to 3.0-3.5, and a white silica precipitate will form; filter and collect the precipitate, wash repeatedly with deionized water until the pH of the filtrate is 6.8-7.2, and dry with forced air at 105℃ to obtain rice husk ash source nano-silica; The mass-to-volume ratio of the rice husk ash to the 20% sodium hydroxide aqueous solution is 1g:3~4ml; the nano-silica particles of the rice husk ash source have a particle size of 20~50nm; 2) The rice husk ash source nano-silica obtained in step 1) is uniformly dispersed in an ethanol-water mixed solution, and then vinyltrimethoxysilane is added. The mixture is stirred at a constant temperature of 55-65℃ for 2-3 hours, filtered, and dried to obtain rice husk ash source hydrophobic nano-silica. The mass ratio of ethanol to water in the ethanol-water mixture is 3-4:1; the mass ratio of rice husk ash source nano-silica, ethanol-water mixture and vinyltrimethoxysilane is 1:8-12:0.15-0.
25.
10. The preparation method of the hyperbranched bio-based silicone ether composite nano defoamer according to claim 1, characterized in that: Includes the following steps: By weight, 84-88 parts of star-shaped hyperbranched bio-based silicone ether copolymer were added to a reactor and heated to 88-90°C. Then, 1.5-2.5 parts of rice husk ash-derived hydrophobic nano-silica were added and stirred for 20-30 min. Next, 3.0-4.5 parts of bio-wax and 3.5-4.5 parts of bio-based emulsifier were added. After high-speed dispersion at 1100-1400 rpm for 0.6-0.8 h, the temperature was lowered to 25-30°C at a rate of 5-8°C / min to obtain hyperbranched bio-based silicone ether composite nano-defoamer.
Citation Information
Patent Citations
Preparation method for allyl-terminated hyperbranched polyether polyol
CN106554494A
Energy-curing breathable coatings (combined)
US20080305349A1